Pengaruh Disiplin Terhadap Kinerja Pegawai Pada Puskesmas Rantau Panjang Peureulak Aceh Timur - Baihaki; Refi , T. Muana (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi, 2023)
The research objective was to determine the effect of work discipline on the performance of PUSKESMAS Rantau Peureulak Health Center employees. The distribution of questionnaires as primary data to a sample of 24 employees, then the results of the questionnaires were tabulated and analyzed and finally tested the hypothesis with the t test. From the research results, the average performance value on a scale of 4 or agrees with the proposed questionnaire means that the level of employee performance at the Rantau Panjang Peureulak Health Center in East Aceh District is running well, and also work discipline shows an average value on a scale of 4 or agrees. The simple linear regression value Y = 16.722 + 0.485X indicates that if the work discipline value is increased by 1 then the performance value increases by 0.485. Then the value of the correlation coefficient (r) is 0.611 which indicates a fairly strong relationship between variables, while the value of the coefficient of determination (r2) is 0.374 or 37.4% which indicates performance is influenced by discipline factors, while the remaining 62.6% is influenced by other factors which were not examined in this study such as the influence of salary, motivation, and work environment. And based on the t test obtained tcount 3.625 > ttable 1.994 and tsig <5% or 0.00 <0.05, this shows the hypothesis of the Effect of Work Discipline on Employee Performance at the Rantau Peureulak Health Center is accepted. And it is suggested to the PUSKESMAS Rantau Peureulak Health Center in East Aceh Regency to further improve the work discipline of its employees by implementing rules and exemplary.